Yogic Practices as a Complementary Approach to Physical Fitness: An Intervention Study - Pramanik, Tarak Nath; Rahaman, Aminur; Saha, Gopal Chandra; Roy, Anupam; Pradhan, Punam (Physical Education Theory and Methodology, 2025)
Background. Yoga is an ancient practice that has gained attention for its potential benefits on muscular strength and endurance, flexibility, power, agility, balance, reaction time, and body mass index (BMI), making it an effective complementary approach for improving overall health and physical fitness. Objectives. This study aimed to evaluate the effects of a six-week yogic regimen on overall health and physical fitness in male university students. Materials and Methods. Forty male students, aged 18 to 24, from the University of Delhi were randomly assigned to an experimental group or a control group, each comprising 20 participants. The experimental group underwent a six-week yogic intervention, including asanas, pranayama, and meditation, conducted daily under the guidance of certified instructors. The control group continued their usual daily routines. Pre- and post-intervention measurements were conducted to assess muscular strength, muscular endurance, flexibility, power, agility, balance, reaction time, and BMI. Data analysis involved both descriptive statistics and inferential statistics (paired and independent sample t-tests) using SPSS software (version 25), with a significance level set at α = 0.05. Results. The experimental group showed considerable improvements in muscular strength, muscular endurance, flexibility, power, agility, balance, reaction time, and BMI (p < .005). In contrast, the control group did not exhibit any notable changes in these parameters. Pre-test comparisons revealed no substantial differences between the experimental and control groups across any variables. However, post-test comparisons between the groups demonstrated significant differences in several key areas: muscular strength, muscular endurance, balance, and reaction time (p < .005). Conversely, no major differences were observed in flexibility, power, agility, or BMI (p > .005). Conclusions. A six-week yogic intervention effectively enhances muscular strength, muscular endurance, flexibility, power, agility, balance, and reaction time, while reducing BMI in university students. Incorporating yoga into physical education and individualized training programs has the potential to significantly enhance fitness outcomes across diverse populations.